Is Strong Interaction - A Cosmological Manifestation? (Global Journal of Science Frontier Research, 2012)
Even though Hubble volume is virtual in the flat universe, by considering the product of critical mass density and the Hubble volume, one can estimate the Hubble mass. By coupling the Hubble mass with the Mach's principle, one can understand the origin of cosmic, atomic and nuclear physical parameters. Thus the four fundamental interactions can be studied in a unified manner. In this connection it can be suggested that, proton mass, nuclear binding energy and strong interaction range are cosmic variables and not fundamental physical constants. Molar electron mass is the planck scale mass of the proton.
Keywords: Hubble volume; Hubble mass; Molar electron mass; Proton mass; Proton size; Nuclear binding energy constants; Potential energy of electron in Hydrogen